HISTORISITAS HADIS MAUDHU'I - Burhanuddin A. Gani (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2017)
This paper directs the study of history, looking at the early emergence of Maudhu '' (false) and the causes and the occurrence of the false hadiths. This discussion is touched on books and books dealing with the contents of ulumul hadith as a whole, both Arabic and Indonesian, books and books as a research material for obtaining primary and accountable data. Mushthafa As-Siba'i concluded that since the period of tabi'in the hadis counterfeit attempt has begun, both in the kibaru At-tabi'in (the tabi'in which at the time of the companions have grown up), as well as during Shiqhar At-Tabi'in (Pre-tabi'in in childhood is still a kid). At the time of the At-Tabi'in kibaru the production of false tradition is still relatively small when compared to the shiqharu at-tabi'in time, with reason: 1. The big tabi'in more appreciate the authority of the Prophet compared with the small tabi'in; 2. His behavior is more eminent in the values of taqwa and religious taqwa; 3. The difference in political temperatures is not so sharp and yet extensive; 4. There are many among friends and tabi'in who emit scholarship and honesty; 5. Their delights in separating the hadith of shahih and maudhu 'is closer to the truth; 6. They are more open the good secret and straighten out something that is not good, to avoid the fake hadiths.